2021
DOI: 10.1002/hbm.25297
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for interhemispheric imbalance in stroke patients as revealed by combining transcranial magnetic stimulation and electroencephalography

Abstract: Interhemispheric interactions in stroke patients are frequently characterized by abnormalities, in terms of balance and inhibition. Previous results showed an impressive variability, mostly given to the instability of motor-evoked potentials when evoked from the affected hemisphere. We aim to find reliable interhemispheric measures in stroke patients with a not-evocable motor-evoked potential from the affected hemisphere, by combining transcranial magnetic stimulation (TMS) and electroencephalography. Ninteen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 60 publications
1
37
3
Order By: Relevance
“…Furthermore, MEPs reflect cortical excitability in only motor cortex but not non-motor brain regions. Concurrent use of TMS and electroencephalography (EEG) (i.e., TMS-EEG) would overcome the drawbacks of MEP measurements, which offers a chance to simultaneously monitor cortical activity in both stimulated area and the interconnected cortical networks ( Casula et al, 2021 ). Importantly, as TMS-EEG can directly measure cortical reactivity and oscillatory dynamics regardless of the integrity of corticospinal tracts ( Borich et al, 2016 ), it allows for investigating neural effects induced by iTBS in stroke survivors without recordable MEPs ( Pellicciari et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, MEPs reflect cortical excitability in only motor cortex but not non-motor brain regions. Concurrent use of TMS and electroencephalography (EEG) (i.e., TMS-EEG) would overcome the drawbacks of MEP measurements, which offers a chance to simultaneously monitor cortical activity in both stimulated area and the interconnected cortical networks ( Casula et al, 2021 ). Importantly, as TMS-EEG can directly measure cortical reactivity and oscillatory dynamics regardless of the integrity of corticospinal tracts ( Borich et al, 2016 ), it allows for investigating neural effects induced by iTBS in stroke survivors without recordable MEPs ( Pellicciari et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the inconsistency could also derive from the potential asymmetry of S-IHI and its association with mirror activity. According to a recent study showing functional relevance of the symmetry of interhemispheric propagation for stroke patients (Casula et al 2021 ), the potential symmetry/asymmetry of IHI and its association with bimanual movement control have to be addressed in more detail in upcoming studies. Nevertheless, the degree of S-IHI rest could still represent behavioral relevance for bimanual movement control (Hübers et al 2008 ; Wahl et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a study in which interhemispheric functional connectivity in EEG was not apparent at rest, TEPs were used to unmask interhemispheric functional connectivity in chronic stroke patients ( 117 ). Casula et al observed that single-pulse TMS pulses on contralesional created a significant interhemispheric imbalance, which led to suppression of the activity in the lesioned hemisphere ( 123 ). Furthermore, patients who later experienced a better recovery showed more balanced TMS-evoked activity between hemispheres.…”
Section: Eeg Combined With Tmsmentioning
confidence: 99%